DEVELOPMENT OF OFFLINE DIGITAL MEDIA PORTALS TO IMPROVE SCHOOL LITERATION IN SMKN 1 BENGKULU CENTRAL - Lovi Triono; Turdjai Turdjai (DIADIK, 2018)
The purpose of this study is to develop a digital media based offline learning  resource portal  to improve school literacy. The research method uses the "Research and Development" approach. The research subjects were teachers and students of SMKN 1 Bengkulu Tengah. Data collection techniques using observation techniques, questionnaires, and  assessment  of the results of the work of making a network design. Media development was validated and verified by media experts and network experts showing that the media was worthy of being  used in a very good category. Based on the analysis carried out in this study, conclusions were taken. (1) Offline digital media-based learning source portals were developed containing the provision of electronic book, video, audio and poster materials as well as containers for student work. (2) Offline media based digital resource learning portal is an effective medium in the provision of literacy materials to improve school literacy. The learning outcomes of the availability of offline digital media with t-test on the experimental group posttest and control group obtained t-count able t-table, so there were significant differences in the work of school literacy before and after the offline digital media-based learning resource portal so that respondents considered the digital-based learning resource portal. offline media is feasible to use in improving school literacy.